2002
DOI: 10.1200/jco.2002.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Yttrium-90–Labeled Ibritumomab Tiuxetan Radioimmunotherapy Versus Rituximab Immunotherapy for Patients With Relapsed or Refractory Low-Grade, Follicular, or Transformed B-Cell Non-Hodgkin’s Lymphoma

Abstract: Radioimmunotherapy with (90)Y ibritumomab tiuxetan is well tolerated and produces statistically and clinically significant higher ORR and CR compared with rituximab alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
547
9
21

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,035 publications
(587 citation statements)
references
References 40 publications
10
547
9
21
Order By: Relevance
“…To date, successful treatment regimens using RIT have been demonstrated, as mentioned, with FDA approved 90 Yttrium 90 Y -2B8 or Zevalin (Witzig et al, 2002), and with 131 I -B1 Tositumomab or Bexxar (Kaminski et al, 2001), both anti-CD-20 mAbs for the treatment of B-cell lymphoma. Several clinical trials are being evaluated.…”
Section: Radioisotopes Immunoconjugatesmentioning
confidence: 99%
“…To date, successful treatment regimens using RIT have been demonstrated, as mentioned, with FDA approved 90 Yttrium 90 Y -2B8 or Zevalin (Witzig et al, 2002), and with 131 I -B1 Tositumomab or Bexxar (Kaminski et al, 2001), both anti-CD-20 mAbs for the treatment of B-cell lymphoma. Several clinical trials are being evaluated.…”
Section: Radioisotopes Immunoconjugatesmentioning
confidence: 99%
“…Long-term follow-up of this cohort demonstrated that many of these responses were durable, indeed 24% of responders had a TTP of more than 3 years (Gordon et al, 2004). In the pivotal phase III study, 143 rituximab naive patients with relapsed or refractory disease were randomized to receive either Y 90 ibritumomab tiuxetan or rituximab administered according to the standard schedule (Witzig et al, 2002b). The majority of patients enrolled had FL, with 17 non-follicular low-grade lymphomas and 13 patients with disease transformation.…”
Section: Tositumomabmentioning
confidence: 99%
“…For this population of patients who had essentially exhausted other available treatment options, Zevalin was shown to be highly effective. The second pivotal study, a phase III randomized, controlled trial, was conducted among 143 patients with relapsed or refractory low-grade follicular or transformed B-cell NHL [26]. Of them, 73 patients who received the Zevalin therapeutic regimen (which includes Rituxan) showed an 80% ORR, compared to 56% ORR in the remaining 70 patients who received Rituxan alone.…”
Section: Y-ibritumomab (Zevalin ® )mentioning
confidence: 99%